Dementia knowledge and attitudes among registered nurses and student nurses - Cheng, Patricia Lynne D.G; Canlas, Katherine Marie T.; Canonizado, Erika Anne M.; Cruz, Meredith Chelsea A.; Cordon, Joyce C.; Cubarrubias, Deanna Lis Pauline F.; Cuevas, Modylyn Grace S.; Verzosa, Ma. Eliza Patrice
Background: Dementia is an increasingly common condition worldwide (Tullo & Gordon, 2013). Front-line health care providers, especially nurses, need to be better equipped with competent knowledge and skills to provide quality care for clients with dementia (Smyth, et al.,2013). Student nurses may care and have direct exposure to their clinical placements in their undergraduate program and in the professional field once they graduate (Scerri & Scerri, 2012). However, it was found that gaps in knowledge regarding dementia can occur even among health professionals. A common misconception for people to associate dementia as a normal part of aging (Cahill, et. al. 2015).